Strawberry Crown Plugs Provide Flexibility and Improved Performance in Cold Climate Plasticulture Production - C. A. Weber (Agronomy, 2021)
Annual plasticulture strawberry production has not been adopted as rapidly in cold climate regions as has occurred in warmer production areas due to uncertainty about potential benefits. Recent trials have demonstrated the potential of regionally adapted varieties in the annual plasticulture system in cold regions, but optimal production practices have not been determined. Summer planting of short-day varieties in these areas would increase flexibility for growers, allowing additional cropping options and improved land use management. The performance of six short-day strawberry varieties (Chandler, Clancy, Jewel, Ovation, Seneca and Ventana) was examined in a series of four annual production trials using cold-stored bare-root crowns for spring planting or a new type of planting stock termed a ‘crown plug’ for two summer plantings. Procedures for producing crown plugs from cold-stored crowns are described. The crown plug summer plantings significantly outperformed the spring planted bare-root plants across all varieties. The July planting established using crown plugs had higher yield and higher mean berry weight across all six varieties compared to the May bare-root planting (623 g/plant—12.5 g mean fruit weight vs. 330 g/plant—10.6 g mean fruit weight, respectively). In the July planting, ‘Seneca’, ‘Ventana’ and ‘Jewel’ exceeded the mean yield per plant for the planting as a whole and the other three varieties also produced more than previously reported for the May planting established with bare-root plants. The August crown plug planting was less productive than the July planting (623 g/plant vs. 498 g/plant, respectively) but was still more productive than both spring plantings. No difference was observed between the April and May plantings across the six varieties. Utilizing crown plugs also reduced the duration of weed control measures needed, improved efficiency of setting plants and limited the need for blossom and runner removal in the field, thus demonstrating labor cost savings that can offset the cost of crown plug production while also producing higher overall yield and mean fruit weight in the varieties in the trial. The summer plantings established with crown plugs demonstrated improved survival through a second winter dormancy period but produced relatively poor yield and berry size in the second harvest season. Crown plugs provide flexibility and improved productivity for growers utilizing annual plasticulture production in cold climate regions.